2022
DOI: 10.1002/hbm.25992
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐related reorganization in the primary somatosensory cortex of patients with postherpetic neuralgia

Abstract: Studies on functional and structural changes in the primary somatosensory cortex (S1) have provided important insights into neural mechanisms underlying several chronic pain conditions. However, the role of S1 plasticity in postherpetic neuralgia (PHN) remains elusive. Combining psychophysics and magnetic resonance imaging (MRI), we investigated whether pain in PHN patients is linked to S1 reorganization as compared with healthy controls. Results from voxel-based morphometry showed no structural differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…A study reported that decreased connectivity in the posterior domains of the DMN in lung cancer patients after chemotherapy (Simó et al, 2018). Besides, chemotherapy-induced disturbances of interactions within and between networks also were discovered, which mainly include executive control, sensorimotor, attentional, and auditory networks (Hu et al, 2022). Consistent with these studies, we found widespread hypo-FCs across important functional networks in lung cancer patients, which may be related to chemotherapeutic agents easily causing demyelination and neuro-in ammation in the brain directly or indirectly (Janelsins, Kesler, Ahles, & Morrow, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A study reported that decreased connectivity in the posterior domains of the DMN in lung cancer patients after chemotherapy (Simó et al, 2018). Besides, chemotherapy-induced disturbances of interactions within and between networks also were discovered, which mainly include executive control, sensorimotor, attentional, and auditory networks (Hu et al, 2022). Consistent with these studies, we found widespread hypo-FCs across important functional networks in lung cancer patients, which may be related to chemotherapeutic agents easily causing demyelination and neuro-in ammation in the brain directly or indirectly (Janelsins, Kesler, Ahles, & Morrow, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The SOM, including somatosensory and motor regions, plays a critical role in the eventual processing of sensation and the execution of motor functions (Stinear, Coxon, & Byblow, 2009). Previous studies have demonstrated that FCs in the somatosensory cortex were disrupted in response to pain stimulation (Chang, Fabrizi, & Fitzgerald, 2022; Lee, Lee, Lee, & Woo, 2022; Li et al, 2022). Similarly, we found that hyper-connectivity between the somatomotor cortex was associated with cancer pain, and the connectivity strength increased with pain duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many fields, from oncology and cardiology to internal medicine, have developed biomarkers that indicate specific pathophysiological mechanisms. In recent years, the combination of machine‐learning‐based MVPA approaches and neuroimaging data features has yielded some encouraging diagnostic and predictive models for individual‐level disease diagnosis and efficacy prediction (H. Li et al, 2022 ; Pang et al, 2022 ; Zhang et al, 2022 ). However, it is still in the early stages of brain biomarker development; future applications should extend our predictive model to multiple time‐visits longitudinal experimental designs, such as predicting the effect of pharmacological and non‐pharmacological therapies on insomnia by collecting data from two time points observed before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…from oncology and cardiology to internal medicine, have developed biomarkers that indicate specific pathophysiological mechanisms. In recent years, the combination of machine-learning-based MVPA approaches and neuroimaging data features has yielded some encouraging diagnostic and predictive models for individual-level disease diagnosis and efficacy prediction (H Li et al, 2022;Pang et al, 2022;Zhang et al, 2022)…”
mentioning
confidence: 99%